A sensitive and group-specific monoclonal antibody-based indirect competitive ELISA for the determination of salbutamol in swine meat and liver samples. Issue 39 (3rd October 2017) - Yuan, Yin; Zhao, Yingying; Wu, Kang; Yang, Hong; Zhao, Kang; Li, Jianguo; Deng, Anping
Abstract : The use of salbutamol (SAL) has been prohibited as an additive in animal feeds for livestock production in many countries due to its harmful effect to the consumers. Abstract : The use of salbutamol (SAL), a β-adrenergic receptor agonist (β-agonist) that could enhance the lean meat-to-fat ratio in livestock, has been prohibited as an additive in animal feeds for livestock production in many countries due to its harmful effect to the consumers. Herein, we present a sensitive and group-specific ELISA based on monoclonal antibodies (mAb) for the determination of SAL in swine meat and liver samples. The SAL derivative, containing the carboxylic group, was prepared by directly reacting SAL with succinic anhydride and then the derivative was linked to carrier proteins. Mice immunized with SAL–bovine serum albumin (BSA) conjugate were utilized for mAb generation. A hybridoma clone (1C3) specifically secreting mAb against SAL with higher sensitivity was successfully obtained. Under optimal conditions, the IC50 and LOD values of the mAb-based ELISA for SAL were calculated to be 0.47 ng mL −1 and 0.049 ng mL −1, respectively, indicating high sensitivity of the assay. The mAb displayed high cross-reactivity (CR) with four β-agonists, i.e., clenbuterol (55%), terbutaline (44%), brombuterol (33%) and cimbuterol (134%) because these compounds contain the same tert -butyl group on the nitrogen atom as does SAL. The CR of the mAb with other β-agonists, including cimaterol, clorprenaline, isoprenaline, neophryn, ractopamine and phenylethylamine A, was less than 2.2% due to relatively large structural differences compared to that of SAL. Swine meat and liver samples were spiked with different SAL content and detected by ELISA. The recovery rates were found in the range of 76.4–107.6% and 71.8–106.8%, respectively, with coefficients of variation less than 20%. Spiked samples were also analyzed by HPLC. A good correlation between both methods was obtained. These results demonstrated that the proposed ELISA is a feasible quantitative/screening method for SAL analysis in swine meat and liver samples. In addition, the recovery results of the β-agonists that displayed the high CR values with mAb in an additional spiking experiment revealed that the ELISA could also be an alternative method for multiple β-agonist detection.